Potential assessment of micro algal lipids: A renewable source of energy. Issue 3 (June 2017) - Arvindnarayan, Sundaram; Sivagnana Prabhu, Kandasamy K.; Shobana, Sutha; Pasupathy, A.; Dharmaraja, Jeyaprakash; Kumar, Gopalakrishnan
Abstract: Two micro algal species namely Chlorella vulgaris (C 1 ) and Chlorella sp. (C 2 ) were selected for the viability of bio-oil production by transesterification in the presence of Ni/H2 catalyst supported with Ni(II)-Schiff base chelate promotor. By this method about 92% of low viscous bio-oil is obtained. Systematic characterizations of the extracted lipids with proximate, elemental and spectral techniques (FT-IR, UV-vis, GC-Mass, 1 H NMR and 13 C NMR) have been carried out to measure their composition profile. Thermogravimetry (TG/DTA) of the wet micro algal biomass, micro algal feed stock and bio-oil has also been performed to analyze their thermal behavior. In addition, scanning electron microscopic pictographs (SEM) were taken for analyzing the micro algal structure before and after the lipid extraction. The fuel properties of the extracted bio-oil were assessed using standard methods and compared to the standards. The bio-oil samples were tested for their remarkable in vitro biological and nuclease activities. In addition, the engine performance (brake specific fuel consumption and brake thermal efficiency) using five types of fuels namely diesel (B100), C 1 micro algal bio-oil 20% blend ( C 1 B20), C 2 micro algal bio-oil 20% blend ( C 2 B20), C 1 micro algal bio-oil 50% blend ( C 1 B50) and C 2 micro algal bio-oil 50% blend ( C 2 B50) and emission characteristics (CO2, NOx, exhaust and smoke) were studied for the bio-oil–diesel blends. Graphical abstract: Two microalgal species namely Chlorella vulgaris (C 1 ) and Chlorella sp. (C 2 ) were selected for the viability of bio-oil production. Systematic characterizations of the extracted lipids with proximate, elemental and spectral tecniques have been carried out to measure the composition profile. Thermogravimetry of the wet microalgal biomass, microalgal feed stock and bio-oil has also been performed to analyze their thermal behavior. In addition, scanning electron microscopic pictographs (SEM) were taken for analyzing the microalgal structure before and after the lipid extraction. The fuel properties of the extracted bio-oil were assessed using standard methods and compared to the standards. The bio-oil samples were tested for their remarkable in vitro biological and nuclease activities. In addition, the engine performance using five types of fuels were tested on DI, air cooled Kirloskar DM10 diesel engine of 110 bhp power with single cylinder of capacity 984 cc and emission characteristics were also studied for the bio-oil–diesel blends. Highlights: Extraction of low density and low viscous algal bio-oil by our extraction path. Spectral and fuel characterization supports the Chlorella species can be considered as a doable feedstock for bio-oil production. SEM and TG/DTA facilitate to design the extraction process and bio-oil applications respectively. C 2 B50 blend exemplifies an enhancement on comparison with petrodiesel. Green house gas emissions were reduced for all the tested blends.